Imaging of Acute Appendicitis in Children - Ferguson, Mark R.; Wright, Jason N.; Ngo, Anh-Vu; Desoky, Sarah M.; Iyer, Ramesh S. (Journal of Pediatric Infectious Diseases, 2017)
Acute appendicitis is a common cause of abdominal surgery in children, and is the result of appendiceal luminal obstruction and subsequent inflammation. The clinical presentation is often variable, allowing imaging to play a central role in disease identification and characterization. Ultrasound is often the modality of choice for diagnosis of appendicitis in children. Ready availability and lack of ionizing radiation are attractive features of sonography, though operator dependence is a potential barrier. Computed tomography (CT) was historically the preferred modality in children, as in adults, but recent awareness of the risks of radiation has reduced its usage. The purpose of this article is to detail the imaging findings of appendicitis in children. The discussion will focus on typical signs of appendicitis seen on ultrasound, CT, and magnetic resonance imaging. Considerations for percutaneous drainage by interventional radiology will also be presented. Finally, the evolution of imaging algorithms for appendicitis will be discussed.
Keywords: appendicitis; ultrasound; CT; MR; interventional radiology drainage; imaging algorithm; appendectomy